Self-compassion, social rank, and psychological distress in athletes of varying competitive levels. (September 2020) - Walton, Courtney C.; Baranoff, John; Gilbert, Paul; Kirby, James
Abstract: Background: Self-Compassion may be seen as a concept contrary to the aims of athletes engaged in competitive sport. This could be accentuated at more elite levels, where athletes may view concepts like self-criticism and self-judgement as more important for improvement. Objectives: The current study aimed to better understand how athletes of different competitive levels (from social to international) relate to concepts of self-compassion. Further, we aimed to explore how factors relating to social rank and self-compassion contribute to psychological distress. Design: Cross-sectional online survey. Method: An online survey was distributed, including the following validated questionnaires: Depression Anxiety and Stress Scales, the Self-Compassion Scale, Fears of Compassion Scales, Social Comparison Scale, Forms of Self-Criticising/Attacking & Self-Reassuring Scale, and the Striving to Avoid Inferiority Scale. Results: Two hundred and fifty-three participants responded to the survey, including 115 recreational and 79 competitive athletes. There were no differences between groups on any measure of compassion or social rank. In a multiple linear regression model, lower self-compassion, higher fears of compassion (for self), and higher feelings of inadequacy predicted more pronounced psychological distress in athletes. Conclusions: Contrary to expectation, the results suggest that even highly elite athletes may be open to using self-compassion. Given that reduced self-compassion and sense of social rank contributed to psychological distress in athletes, the results suggest that compassion-based approaches to treating psychological distress in this population may be valid. Highlights: We explored social rank and self-compassion measures in a competitively diverse sample of athletes and non-athletes. We anticipated that athletes competing at a higher level would report less self-compassion and higher fears of compassion. There was no difference in any measure of compassion amongst groups. Self-compassion, fears of compassion (for self), and feelings of inadequacy predicted psychological distress in athletes. Findings suggest compassion-based approaches to treating psychological distress may be appropriate in athletes.